Exploration of biomarkers to predict clinical improvement of atopic dermatitis in patients treated with dupilumab: A study protocol. Issue 38 (18th September 2020) - Nakahara, Takeshi; Izuhara, Kenji; Onozuka, Daisuke; Nunomura, Satoshi; Tamagawa-Mineoka, Risa; Masuda, Koji; Ichiyama, Susumu; Saeki, Hidehisa; Kabata, Yudai; Abe, Riichiro; Ohtsuki, Mamitaro; Kamiya, Koji; et al.
Abstract: Background: Atopic dermatitis (AD) is a common eczematous skin disorder that profoundly reduces the quality of life due to intractable pruritus. Excellent therapeutic success of the anti-interleukin 4 receptor-α antibody dupilumab in clinical trials and a real-world clinical context indicates the crucial roles of interleukin (IL)-4 and IL-13 in the pathogenesis of AD. Along with the clinical improvement in skin scores and pruritus, dupilumab significantly and progressively reduces and normalizes the upregulated expression of T helper type 2 signatures such as Chemokine (C-C motif) ligand (CCL)17, CCL18, CCL22, and CCL26 in the lesional skin of AD. However, no blood/serum biomarkers are known to predict good or poor outcome in patients with AD treated with dupilumab. Methods: Patients are at least 18 years of age and have moderate-to-severe AD with Eczema Area and Severity Index (EASI) ≥16, Investigator's Global Assessment ≥3, and body surface area ≥10%. We are going to enroll more than 130 subjects from 18 medical facilities. Clinical objective findings will be evaluated by EASI. Subjective symptoms will be assessed by Patient-Oriented Eczema Measure, Numerical Rating Scale for Pruritus (Pruritus-NRS), Skin Comfort-NRS, and Treatment Satisfaction-NRS. We will measure 18 blood/serum biomarkers including % eosinophils in blood cell count, lactate dehydrogenase, total IgE, soluble interleukin 2 receptor, CCL17, CCL18, CCL22, CCL26, CCL27, IL-13, IL-22, IL-24, IL-25, IL-31, IL-33, thymic stromal lymphopoietin, periostin, and squamous cell carcinoma antigen-2. The clinical evaluation and biomarker sampling will be performed at 0, 2, 4, 8, and 16 weeks of dupilumab treatment. We will also perform proteomic analysis (of roughly 300 proteins) of the patients' sera obtained at 0 and 2 weeks of treatment. The primary endpoint is the association between "baseline levels of 18 biomarkers" and "% change from baseline of EASI at 16 weeks of dupilumab treatment." Discussion: This is the first clinical trial to explore the biomarkers, including potential proteomic markers, most strongly associated with improvement in EASI in patients with moderate-to-severe AD treated with dupilumab for 16 weeks (B-PAD study). A limitation is that we will only enroll Japanese patients.